2021
DOI: 10.3390/antiox10071088
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative-Signaling in Neural Stem Cell-Mediated Plasticity: Implications for Neurodegenerative Diseases

Abstract: The adult mammalian brain is capable of generating new neurons from existing neural stem cells (NSCs) in a process called adult neurogenesis. This process, which is critical for sustaining cognition and mental health in the mature brain, can be severely hampered with ageing and different neurological disorders. Recently, it is believed that the beneficial effects of NSCs in the injured brain relies not only on their potential to differentiate and integrate into the preexisting network, but also on their secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 167 publications
(229 reference statements)
0
9
0
Order By: Relevance
“…stress (Santos et al 2021). On the other hand, Aβ peptides (e.g., Aβ42 peptides) could favor neurogenesis of neural stem cells by promoting the migratory potential of neural stem cells toward inflamed lesions in animal brains (López-Toledano and Shelanski 2004).…”
Section: The Influence Of Tissue Microenvironment On Stem Cell Fate I...mentioning
confidence: 99%
“…stress (Santos et al 2021). On the other hand, Aβ peptides (e.g., Aβ42 peptides) could favor neurogenesis of neural stem cells by promoting the migratory potential of neural stem cells toward inflamed lesions in animal brains (López-Toledano and Shelanski 2004).…”
Section: The Influence Of Tissue Microenvironment On Stem Cell Fate I...mentioning
confidence: 99%
“…54,55 The proliferation and migration of neural precursor cells can be inhibited by reactive oxygen species (ROS). 56,57 To aid the removal of ROS, mammals possess a set of antioxidant defense systems that are composed of various functional components, including nonenzymatic and enzymatic antioxidants. There are multiple antioxidant enzymes, such as SODs, catalase, and GPXs, which play a vital role in neurogenesis in the hippocampal DG region throughout neurodevelopment.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Melatonin is widely accepted as nature’s defense against ROS, and it improves the genomic function and the expression of antioxidant enzymes, including SOD, GPX, and catalase. , Neural tissue is especially vulnerable to oxidative damage induced by aging, brain injury, and neurological diseases. , The proliferation and migration of neural precursor cells can be inhibited by reactive oxygen species (ROS). , To aid the removal of ROS, mammals possess a set of antioxidant defense systems that are composed of various functional components, including nonenzymatic and enzymatic antioxidants. There are multiple antioxidant enzymes, such as SODs, catalase, and GPXs, which play a vital role in neurogenesis in the hippocampal DG region throughout neurodevelopment. , We previously reported that miR-451 could protect erythroid cells from damage related to oxidative stress by repressing the expression of 14-3-3zeta .…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al [ 12 ] stated that adipose derived stem cell-secretome can provide anti-free-radical effects and reduce oxidative stress with the expression of F2-Isoprostane. Honmou et al [ 13 ] also stated that mononuclear stem cell secretome in SCI inhibited microvascular obstruction and thrombosis, promoted vasodilation, immunomodulation, and neuroprotection, while Santos et al [ 14 ] and Yang et al [ 15 ] stated that NSC-secretome in SCI stimulated the transformation of phenotype M1 to phenotype M2 of macrophages, microglia, and astrocytes through PgE2, IL-10, TGF-β, proliferator-activated receptor gamma[ 14 , 15 ]. Macrophage M2 secreted anti-inflammatory cytokines IL-4, IL-10, TGF-β, and hepatocyte growth factor, whereas macrophage M1 secreted pro-inflammatory cytokines IL-1, IL-6, IL-8, TNF-α, MMP9, and F2-Isophostane[ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%